Controle de torque em laminador de soja buscando eficiência energética - Michelin, Danilo Expedito (2021)
Currently, the national agro-industry is in full development, both in expansion and in terms of technology. For this development, it is important to take into account the energy demand, as well as the environmental impact. In the private sector, in addition to the need for development, there is also a need to improve models and techniques already used, aiming at increasing productivity and, consequently, profits. The objective of this work was to improve the efficient use of electric energy using frequency inverters to control torque in the soy rolling motors, a process that is responsible for a large part of the electric energy consumption in the crushing industries. To achieve this objective, the proposed methodology was based on calculations and theories that verified the possibility of improving the performance of the rolling mills. Thus, in practice, frequency inverters were installed in two rolling mills, which had their electricity consumption monitored before and after the installation of the frequency inverters. During the tests, it can be seen that there was no improvement in terms of cost reduction with electricity consumption, it was found, however, that there was an improvement in relation to power quality, another point evaluated was the need to reassess the currently installed capacitor bank in the factory.